A Randomized Clinical Trial on Imipramine and Oxybutynin for the Treatment of Children With Primary Nocturnal Enuresis (Bangladesh Journal of Urology, 2020)
Background: Nocturnal enuresis is a common childhood problem. There are several treatment options for the treatment of children with primary enuresis including behavioral modification, drug therapy like tricyclic antidepressant, vasopressin analog and anticholinergic drugs.Objective: To observe the efficacy of oxybutynin and imipramine for the treatment of children with primary nocturnal enuresis in terms of symptom relief and disease control.Materials and methods: A randomized clinical trial was conducted in urology outpatient department, Sir Salimullah Medical College Mitford Hospital, Dhaka from May 2015 to April 2016. Total 70 patients with primary nocturnal enuresis were selected according to selection criteria. After duly taking informed written consent, patients were randomly divided into 2 groups by lottery method. In this way 35 patients were selected as group- A and 35 patients were selected as group-B. Patients of group-A were treated with imipramine and Group-B were treated with oxybutynin.Results: Age range of the subjects was from 5-16 years. Among them 30% of the subjects in the imipramine group were between 7-9 years of age and 30% of the subjects in the oxybutynin group were between 5-7 years of age. The male-female ratio was 1.2:1.Thirty five percent of the subjects had positive family history while remaining 65% did not have such history. At the base line study, 80% of the subjects did not show satisfactory result following 2 weeks of behavioral modification while 20% showed improvement. Before starting drug therapy, 60% patients had 4-5 bed-wetting nights/week. Following treatment, frequency of bed wetting dropped sharply to